Macro Mineral Status of Feds in the Central and Western Parts of Ethiopia - Aschalew Tsegahun; Pornsri Chairatanayuth; Pravee Vijchulata; Sayan Tudsri (Agriculture and Natural Resources, 2006)
Different feed types collected from three altitudinal ranges in the central and western parts of Ethiopia in two different seasons were evaluated for their macro mineral concentrations. Feeds in the selected parts of the country comprised of natural pasture, hay, straws of cereals and food legumes and to a lesser extent cultivated forage crops and agro-industrial by-products. All feed samples were taken directly from the field or supplied by the farmers. The feed samples were analyzed for the macro minerals namely Ca, P, Mg, Na and K. Mineral concentrations were assessed in relation to recommended dietary requirements of sheep. The results indicated a wide variation in macro minerals along with seasons, altitudes, and feed types. Regardless of seasons and altitudes, all feed types were deficient in Na. Natural pasture, cereal straws, cultivated forages and legume straws were found to be deficient in P. Among the macro minerals P, Mg and Na were found to be the most lacking. In situations where forages are fed exclusively, supplementary P, Mg and Na would be required. The insufficiency of Na is the most widespread mineral deficiency in the studied parts of the country. The levels of Ca and K were found to be sufficiently high to meet estimated nutritional requirements of sheep.